The Effect of Repeated Reading Method on Reading Fluence in Slow Learning Students in State Primary Schools - Amaliyah Nur Azizah; Dewi Rosiana; Stephani Raihana Hamdan (International Journal of Pedagogy and Teacher Education, 2025)
Students who receive education at elementary schools consist of regular students and students with special needs, including slow learners. With limited cognitive capacity, students who are slow learners will lack the process of developing general concepts or ideas that underlie many school assignments, especially in language aspects, including reading skills. This research was conducted to determine the effect of the repeated reading method on the reading fluency of slow learners in grade 3 in state elementary schools. Reading fluency will be measured by the subject's speed when reading the entire pretest-posttest text and calculating correct words per minute (WCPM) when the subject reads the pretest-posttest text in the first minute. The research method used in this research is quantitative with a single-case research design, namy the ABA design. The sample in this research was taken based on a non-probability sampling method with purposive sampling. The repeated reading method given to 3 slow learning students in class III at the Griba State Elementary School for 12 days and 5 repetitions of reading the text and 5 times the pronunciation of words that were misread, was able to increase reading speed and accuracy significantly (0.023 and 0.038) based on tests paired sample t-test statistics. So H1 is accepted and H0 is rejected. In line with this, it can be concluded that there is an influence of the repeated reading method on reading fluency in slow learners in state elementary schools.